2023
DOI: 10.1039/d3sc01040f
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of an alkaline environment for electrocatalytic CO2 reduction in acidic electrolytes

Abstract: Acidic electrochemical CO2 reduction reaction (CO2RR) can minimize carbonate formation and eliminate CO2 crossover, thereby improving long-term stability and enhancing single-pass carbon efficiency (SPCE). However, the kinetically favored hydrogen evolution...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Electrochemical CO 2 reduction in the acidic electrolyte is renowned for high CO 2 utilization and mitigated bicarbonate and carbonate formation. 39–43 Benefitted from the PTFE treatment for enhanced hydrophobicity, NiNF-1100 is capable of operating also in the acidic electrolyte such as H 2 SO 4 /K 2 SO 4 (pH = 2, C K + = 0.5 M). Here, we mainly compared NiNF-1100 with NiNF-1100p and NiNC-1100 to assert the advantage of the integral electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical CO 2 reduction in the acidic electrolyte is renowned for high CO 2 utilization and mitigated bicarbonate and carbonate formation. 39–43 Benefitted from the PTFE treatment for enhanced hydrophobicity, NiNF-1100 is capable of operating also in the acidic electrolyte such as H 2 SO 4 /K 2 SO 4 (pH = 2, C K + = 0.5 M). Here, we mainly compared NiNF-1100 with NiNF-1100p and NiNC-1100 to assert the advantage of the integral electrode.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Under flow cell operating conditions, theoretical calculations of SPCE for C 1 (CO, HCOO − ) and C 2 (C 2 H 4 ) chemicals indicate that, in near-neutral electrolytes, the SPCE is 50% for both CO and HCOO − and 25% for C 2 H 4 . 42,52 In alkaline electrolytes, the SPCE is considerably lower, with theoretical results showing 11.7% for CO and HCOO − and 4.2% for C 2 H 4 . 46 However, in acidic electrolytes, 100% SPCE can be achieved because of preventing CO 3 2− formation.…”
Section: Merits Of Performing the Co2rr In Acidic Electrolytesmentioning
confidence: 99%
“…Recently, operating parameters within acidic electrolytes (pH < 2) have received significant interest, chiefly due to their potential to obviate the energy penalties associated with CO 3 2− formation in the CO 2 RR. 9,42–55 However, this approach is a double-edged sword: on the one hand, it promises enhanced energy efficiency, while on the other hand, it presents challenges such as a lowered HER activation barrier and diminished catalyst stability. To judiciously operate the CO 2 RR in acidic media, it is imperative to engineer both catalysts and electrodes capable of attenuating proton permeation or sustaining elevated *CO coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism studies indicated that the carbon shell could limit the H + diffusion to the catalytic active site, thus optimizing the CO 2 /H + concentration ratio for promoting CO 2 RR and simultaneously suppressing HER. Very recently, Gong and co‐workers reported a hollow‐structured Ag@C catalyst for CO 2 RR in acidic conditions, [35] with a 95 % FE of CO at commercial‐related current density and 46.2 % SPCE. The results of mass transport simulations reveal that the Ag@C hollow structure could modulate the diffusion rate of OH − and H + , leading to a high local alkaline environment for excellent catalytic performance (Figure 5b).…”
Section: The Enrichment Strategy In Acidic Co2rrmentioning
confidence: 99%